2023
DOI: 10.1111/jopy.12818
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban differences in personality traits and well‐being in adulthood

Abstract: ObjectiveOne large focus of personality psychology is to understand the biopsychosocial factors responsible for adult personality development and well‐being change. However, little is known about how macro‐level contextual factors, such as rurality–urbanicity, are related to personality development and well‐being change.MethodThe present study uses data from two large longitudinal studies of U.S. Americans (MIDUS, HRS) to examine whether there are rural–urban differences in levels and changes in the Big Five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…Household income was comprised of the sum (in U.S. dollars) of participants' and their spouses' self-reported earnings, pensions and annuities, social security, unemployment and 2 Originally, the preregistration stated the 9-RUCC would be the primary operationalization, and the 3-RUCC would be the sensitivity analysis operationalization. However, 3-RUCC variable was used as the primary operationalization because: (a) conceptually, U.S. Americans think about their geographical residence as either rural, suburban, or urban (Bucholtz et al, 2020;Short Gianotti et al, 2016); (b) prior work has established the convergent validity of operationalizing "rural" as RUCCs 7-9 (J. C. Long et al, 2021;Streeter et al, 2020) and the predictive validity of 3-RUCC for various health outcomes (Atherton et al, 2023;Joseph et al, 2015;Segel & Lengerich, 2020;Wang et al, 2013;Zuniga & Lango, 2018); (c) conceptually and statistically, a 9-category RUCC analyzed as a "continuous" variable has untenable assumptions including that each of the nine scale points are equally distanced and conceptually different from one another; and (d) statistically, using 9-category RUCC as a categorical (or continuous) variable poses methodological problems due to the skewed/non-normal distribution and the small sample sizes at the rural end of the scale, as noted by a biostatistician who consulted on the analytic approach (see Figure S1-S2); 3-RUCC has higher statistical power for the present analyses. ATHERTON 4 workers' compensation, other government transfers, household capital income, and other income in the last calendar year.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Household income was comprised of the sum (in U.S. dollars) of participants' and their spouses' self-reported earnings, pensions and annuities, social security, unemployment and 2 Originally, the preregistration stated the 9-RUCC would be the primary operationalization, and the 3-RUCC would be the sensitivity analysis operationalization. However, 3-RUCC variable was used as the primary operationalization because: (a) conceptually, U.S. Americans think about their geographical residence as either rural, suburban, or urban (Bucholtz et al, 2020;Short Gianotti et al, 2016); (b) prior work has established the convergent validity of operationalizing "rural" as RUCCs 7-9 (J. C. Long et al, 2021;Streeter et al, 2020) and the predictive validity of 3-RUCC for various health outcomes (Atherton et al, 2023;Joseph et al, 2015;Segel & Lengerich, 2020;Wang et al, 2013;Zuniga & Lango, 2018); (c) conceptually and statistically, a 9-category RUCC analyzed as a "continuous" variable has untenable assumptions including that each of the nine scale points are equally distanced and conceptually different from one another; and (d) statistically, using 9-category RUCC as a categorical (or continuous) variable poses methodological problems due to the skewed/non-normal distribution and the small sample sizes at the rural end of the scale, as noted by a biostatistician who consulted on the analytic approach (see Figure S1-S2); 3-RUCC has higher statistical power for the present analyses. ATHERTON 4 workers' compensation, other government transfers, household capital income, and other income in the last calendar year.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…Likewise, most prior investigations either examine dichotomized rural-urban continuum codes or a continuous measure ranging from 1 to 9, whereas the present study operationalizes as 3-RUCC. Prior work demonstrates that quantifying "rural" as RUCCs 7-9 has convergent validity with other definitions of rural (J. C. Long et al, 2021;Streeter et al, 2020) and the 3-RUCC operationalization has predictive validity for various health outcomes (Atherton et al, 2023;Joseph et al, 2015;J. C. Long et al, 2021;Segel & Lengerich, 2020;Wang et al, 2013;Zuniga & Lango, 2018).…”
Section: Limitationsmentioning
confidence: 99%
“…Such an ambitious project-while being attentive to levels of abstraction and appropriately modeling measurement error-can provide the field with guidance on the sources of variance in the characteristics we study and set reasonable expectations for which characteristics are most malleable to environmental changes and interventions. Atherton et al (2023; this issue) examined in two U.S. middle-aged and older adult samples (i.e., HRS, MIDUS) how living in urban vs. rural regions is linked to levels and changes in Big Five traits and well-being (i.e., psychological well-being and life satisfaction). The authors found that living in rural areas was linked to lower openness, conscientiousness, and psychological well-being as well as higher levels of neuroticism.…”
Section: Overview Of Papersmentioning
confidence: 99%
“…Atherton et al (2023; this issue) examined in two U.S. middle‐aged and older adult samples (i.e., HRS, MIDUS) how living in urban vs. rural regions is linked to levels and changes in Big Five traits and well‐being (i.e., psychological well‐being and life satisfaction). The authors found that living in rural areas was linked to lower openness, conscientiousness, and psychological well‐being as well as higher levels of neuroticism.…”
Section: Overview Of Papersmentioning
confidence: 99%
See 1 more Smart Citation